sa fait 121
Tu développes donc ca fait : (3x-6x²+4-8x)-(6-10x) = 0
(-6x²-5x+4)-6+10x = 0
-6x²-5x+4-6+10x = 0
-6x² +10x -2 = 0
Après faut que tu résolves l'équation la

Réponses

2013-11-29T20:07:20+01:00
Bonsoir

(3x + 4 )(1 - 2x ) - 5(1 - 2x) = 0

Factorisons par (1 - 2x)

(1 - 2x)[(3x + 4) - 5] = 0

(1 - 2x) (3x + 4 - 5) = 0

(1 - 2x) (3x - 1) = 0

1 - 2x = 0      ou     3x - 1 = 0
    -2x = -1     ou      3x = 1
      x = 1/2    ou     x = 1/3
2013-11-29T20:10:14+01:00
(1-2x)((3x+4)-5)=0
(1-2x)(3x-1)=0
produit nul quand :1-2x=0 ou 3x-1=0
1=2x. x=1/3
1/2=x